2008
DOI: 10.1016/j.stem.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Evi-1 Is a Critical Regulator for Hematopoietic Stem Cells and Transformed Leukemic Cells

Abstract: Evi-1 has been recognized as one of the dominant oncogenes associated with murine and human myeloid leukemia. Here, we show that hematopoietic stem cells (HSCs) in Evi-1-deficient embryos are severely reduced in number with defective proliferative and repopulating capacity. Selective ablation of Evi-1 in Tie2(+) cells mimics Evi-1 deficiency, suggesting that Evi-1 function is required in Tie2(+) hematopoietic stem/progenitors. Conditional deletion of Evi-1 in the adult hematopoietic system revealed that Evi-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
302
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 263 publications
(320 citation statements)
references
References 38 publications
14
302
2
2
Order By: Relevance
“…Mouse embryos lacking Evi-1 die due to the remarkably decreased number and reconstitution capacity of HSCs. Conditional Evi-1 deletion in adult mice also showed that Evi-1 is essential for the maintenance of HSCs [98]. By knocking in an internal ribosome entry site (IRES)-GFP cassette into the Evi-1 locus, Kataoka et al demonstrated that Evi-1 was predominantly expressed in LT-HSCs, and its expression was sharply down-regulated along with differentiation, indicating that the Evi-1 expression level is a candidate HSC-specific marker.…”
Section: Transcription Factors Regulating Hscsmentioning
confidence: 99%
“…Mouse embryos lacking Evi-1 die due to the remarkably decreased number and reconstitution capacity of HSCs. Conditional Evi-1 deletion in adult mice also showed that Evi-1 is essential for the maintenance of HSCs [98]. By knocking in an internal ribosome entry site (IRES)-GFP cassette into the Evi-1 locus, Kataoka et al demonstrated that Evi-1 was predominantly expressed in LT-HSCs, and its expression was sharply down-regulated along with differentiation, indicating that the Evi-1 expression level is a candidate HSC-specific marker.…”
Section: Transcription Factors Regulating Hscsmentioning
confidence: 99%
“…Although we have shown that complete loss of Evi-1 slightly reduced colony-forming ability of E2A/HLF, the effect of Evi-1 deletion in E2A/HLF-immortalized cells is relatively small than that in MLL-immortalized cells. 12 It therefore seems likely that the Evi-1/HMT interaction is not a major mediator for oncogenic activity of E2A/HLF.…”
Section: Discussionmentioning
confidence: 99%
“…30 We used E2A/HLF as a control because the contribution of Evi-1 to colony-forming ability of E2A/HLF-transduced cells is relatively small. 12 Despite the efficient downregulation of Suv39h1 and G9a (Figure 6e), the HMT-knockdown cells showed equivalent colony-forming activity to that of control E2A/HLF-transduced cells (Figure 6f; Supplementary Table 2). These results indicate that both Suv39h1 and G9a are specifically required for Evi-1-mediated bone marrow immortalization.…”
Section: Both Suv39h1 and G9a Are Required For Efficient Propagation mentioning
confidence: 98%
See 2 more Smart Citations